Joint applicability test of software for laboratory assessment and risk analysis - Pluess, D. N.; Meyer, Thierry; Mašín, Jindřich; Mikulášek, Petr; Ferjenčík, Miloš (Elsevier, 2016)
Most of the available risk management methods are not directly applicable to academic research laboratories. One solution to systematically perform risk analyses in this environment is the Laboratory Assessment and Risk Analysis (LARA) method. This method was developed to allow untrained personnel to identify of possible risks and rank them according to their importance. The purpose of this study was to find out, if this method can be used as a holistic risk management technique in different environments, and which are the differences when comparing the results to other, well established risk analysis techniques. The risk analyses were performed at two European universities and for various procedures. The results show, that the LARA procedure is more easily performable than the other methods and gives comparably adequate results. Being applicable by non-experts, this holistic risk analysis method for research laboratories can help to reduce the accident rate in the academic environment.
Společný test použitelnosti softwaru pro hodnocení a analýzu rizika laboratoří
Keywords: Risk assessment; Risk analysis; Laboratory safety; Hodnocení rizika; Analýza rizika; Bezpečnost laboratoří